2005
DOI: 10.1515/zna-2005-0313
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complex Formation in Melts of Acetamide-Ammonium Nitrate-Water Mixtures, Part I. Cobalt(II) Chloride Complexes

Abstract: has been investigated. Absorption spectra of cobalt(II) chloride containing variable amounts of ammonium chloride were recorded at 45 to 60 • C. In the absence of chloride, the solutions show spectra typical for octahedral co-ordination of cobalt(II). Addition of chloride caused a shift of the absorption maximum toward lower energies and an increase of the molar absorption coefficient with increasing chloride concentration. The position of the absorption maximum and the intensity of the absorption indicate tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In addition, it can be seen that 75 the position of the absorption maximum in the anhydrous system at 544 nm corresponds to the position of the absorption maxima ascribed to dodecahedral [Co(NO 3 ) 4 ] 2− complex species obtained in the anhydrous KNO 3 -LiNO 3 eutectic melt (λ max = 550 nm) 23 and eutectic mixture 0.723CH 3 CONH 2 -0.277NH 4 NO 3 (λ max = 80 538 nm). 24 In the system of [HO(CH 2 ) 2 mim]NO 3 ·3H 2 O an absorption maximum is shifted toward lower wavelengths (approximately at 515 nm) which corresponds to the position of the absorption maximum of octahedral cobalt(II) complexes obtained in the aqueous melt of Ca(NO 3 ) 2 ·4H 2 O (λ max = 512 85 nm) 25 and diluted aqueous solutions (λ max = 513 nm). 26 Addition of chloride ions to cobalt(II) nitrate solution caused a replacement of nitrate ions with chloride and formation of new absorbing species: 5 This change is followed by the change of colour from pale pink to dark blue (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, it can be seen that 75 the position of the absorption maximum in the anhydrous system at 544 nm corresponds to the position of the absorption maxima ascribed to dodecahedral [Co(NO 3 ) 4 ] 2− complex species obtained in the anhydrous KNO 3 -LiNO 3 eutectic melt (λ max = 550 nm) 23 and eutectic mixture 0.723CH 3 CONH 2 -0.277NH 4 NO 3 (λ max = 80 538 nm). 24 In the system of [HO(CH 2 ) 2 mim]NO 3 ·3H 2 O an absorption maximum is shifted toward lower wavelengths (approximately at 515 nm) which corresponds to the position of the absorption maximum of octahedral cobalt(II) complexes obtained in the aqueous melt of Ca(NO 3 ) 2 ·4H 2 O (λ max = 512 85 nm) 25 and diluted aqueous solutions (λ max = 513 nm). 26 Addition of chloride ions to cobalt(II) nitrate solution caused a replacement of nitrate ions with chloride and formation of new absorbing species: 5 This change is followed by the change of colour from pale pink to dark blue (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Some authors have identified only one low intensity complex in aqueous solutions [26,27]. These studies have been extended in molten inorganic salts as well [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Molten acetamide is highly polar solvent and exhibits “water-like” properties and many reports appeared since its exploration as a nonaqueous solvent . A variety of physicochemical properties of molten (acetamide + salt) and (urea + salt) mixtures have already been reported, , , and studies of solute–solvent coupling in these media have also emerged recently. …”
Section: Introductionmentioning
confidence: 99%